Exploring Student Perceptions of Online Vocabulary Games for Learning : A Literature Review - Marwan Putri, Fauziah Fatimah Az-Zahra; Syafitri, Dewi (STKIP PGRI Lubuklinggau, 2024)
Vocabulary acquisition remains a challenge in EFL contexts. This review examines how mobile-assisted online vocabulary games influence learner perceptions and vocabulary development. Through a structured analysis of peer-reviewed studies, we synthesized evidence on engagement, motivation, and retention. Findings indicate that flashcards, quizzes, crosswords, and peer-competition features promote practice, enjoyment, and confidence, while digital distractions, uneven access, and limited teacher readiness present significant barriers. We conclude that embedding mobile vocabulary games within structured curricula and providing targeted professional development enhances their effectiveness. Implications include the need for coherent pedagogical integration; future research should investigate long-term learning trajectories and blended instructional models.